Pengaruh Greenpreneurial Orientation Terhadap Green Purchase Intention Pada Konsumen Produk Ramah Lingkungan - Posmaria Setiasiwi Sitohang; Sentot Suciarto; MY. Dwi Hayu (JEMAP, 2023)
Environmental issue such as global warming, plastic waste, electronic waste which is hazardous  for health, use of preservatives and dyes, others has made society awareness.  Some of society requested  more healthy environment for their life.  Green entrepreneurship orientation in enterpreunership is intangible natural resources.  It push a firm to have the inisiative of advanced environment, which called as green entrepreneurial orientation (GEO).  This research is conducted to know  more preference of a green entrepreneurial oriented company.  Hipotesis test showed that  there is significant positive relationship between entrepreneurial oriented company with purchase interest. This means that  entrepreneurial oriented businessman, who care on green environment, is responded positively by consumers.  Then, those make consumer interested to buy it.